Enhanced DTC induction motor drives for THD minimization performance improvement with multilevel inverter - Siong Kai Chien; Sy Yi Sim; Wahyu Mulyo Utomo; Sie Long Kek; Farahiyah Mustafa; Nor Aira Zambri; Alvin John Lim Meng Siang; Gia Yi Sim (Institute of Advanced Engineering and Science, 2022)
Direct torque control (DTC) is a method applied in induction motor (IM) drives to control the speed and torque of IM accurately and independently without feedback signal. However, in fast fourier transform (FFT) analysis, the total harmonic distortion (THD) of the IM drives is high in DTC method with conventional inverter (CI). Therefore, the purpose of this study is to minimize the THD without affecting the drive’s performance. A DTC IM drive with multilevel inverter (MLI) is proposed in this study to reduce THD and preserve good speed and torque response of IM simultaneously. DTC IM drive with proposed MLI based THD minimization has several advantages over the DTC IM drive with CI, including higher generated output voltage with low distortion, operate under low switching frequency, and work with renewable energy. In order to prove the effectiveness of the proposed MLI based THD minimization in DTC IM drive, MATLAB Simulink is used to investigate the response of the IM drive and THD under different operating condition. From this study, proposed MLI based THD minimization DTC IM drive is able to reduce THD with a maximum of 13% in low speed operation as compared to DTC IM drive with CI.